Rohingya Women in Karachi. Issue 1 (June 2017) - Iqbal, Haya Fatima
Karachi is a sprawling megapolis of Pakistan that hosts hundreds of thousands of immigrants and refugees from different parts of the world. The Rohingyas constitute one such community and live in the south of the city in an area called Arakanabad, named after their ancestral homeland of Arakan (now called Rakhine State) in Myanmar. While there is some media coverage about the plight of the community in general, the challenges faced by migrant Rohingya women are largely ignored. This is a photo essay of Rohingya women living in Karachi.